Geochemical characterization of mineralized albitite from Paleoproterozoic Bhukia IOCG‐IOA deposit of Aravalli‐Delhi Fold Belt, Rajasthan, western India: Genetic linkage to the gold (±Cu ± U) mineralization. (2nd November 2019) - Mukherjee, Rahul; Venkatesh, Akella Satya; Fareeduddin,
Abstract : Paleoproterozoic Bhukia gold deposit is located within the Debari Group of Aravalli Supergroup, Rajasthan, northwestern India. The major lithounits that are associated with gold–graphite (±Cu ± U) mineralization exposed in Bhukia are albitite, carbonates, and quartzite which have undergone upper greenschist to amphibolite facies metamorphism. Ore mineralization viz. pyrrhotite, arsenopyrite, chalcopyrite, pyrite, graphite, magnetite, and goethite in the study area are associated with NNW–SSE trending shear zone. Nuggets of gold are identified in the thick gossan zones that occurs parallel to the shear zone. The gold–sulfide lodes of the Bhukia deposits are largely confined either to marble or albitized marble and pure monomineralic albitite. The mineralization that is associated with the albitite, follows the boundaries of albite grains which confirms the role of these weak zones for the mobilization of mineralizing fluid and concentration of metal ions. Hence, geochemical studies of albitite would help to evaluate the petrogenesis, likely magmatic affinity, tectonic setting, controls of the mineralizing fluid, source, and their linkage to the gold (±Cu ± U) metallogeny. Bhukia albitite is characterized by Na–Al–rich and K‐poor compositions along with metaluminous nature. Geochemical analysis of various key elements suggests that albitite is the product of low‐K calc‐alkaline magma series with variation in Nb/Ta ratio indicating their fractionation during the melt–rock interaction within the shear zone. Geochemical signatures suggest the role of upper continental crust in channelizing the mineralized fluids that generated albitite with felsic to intermediate composition in and around Bhukia deciphered from their low Nb/Y ratios. Lower concentration of compatible elements (Ni and Cr) and higher concentration of incompatible elements (Th, La, and Nd) with SiO2 suggest that evolution of albitite rock is related to the fractional crystallization process. Zr/Hf ratios of 9–35 with the average of 18 suggest that albitite formed under magmatic–hydrothermal transitional environment. Rare Earth Elements (REE) patterns of albitite samples are moderately fractionated showing Light Rare Earth Elements (LREE)‐enrichment with a rather steep slope and exhibit distinct negative Eu anomalies (0.42–0.71, average 0.57). The enrichment of LREE in comparison to the Heavy Rare Earth Elements (HREE) suggests a more evolved source, i.e., process of melting at shallow environments. Tectonic setting of albitite samples suggest their origin in a volcanic arc region that underwent rifting. Detailed geochemical characterization unravelled complex evolutionary history of albitite in the Bhukia area, which attests derivation of the parental melt possibly from an enriched SCLM (Sub‐continental lithospheric mantle) source similar to most of the IOCG‐IOA deposits worldwide.